A Long Road to the Development of Bio-Fuel in Indonesia - Marendra Cahya Sadikin (Jurnal Ilmiah Hubungan Internasional, 2014)
Abstract: Increased energy usage in line with economic growth and the increase in world populationhas an immediate impact for the depletion of fossil -based energy, especially petroleum. The fact thatworld oil supplies are limited, many states are forced to prioritize energy policy as a top priority indevelopment policy. In addition, this condition has raised new fears that the global energy security.With a strong concern of potential extinction of petroleum and other fossil -based energy sources ,policy makers should pay more attention to energy security. The same trend is occurring in Indonesia.Along with the increase in the national population, national and regional development plans, the needfor national energy security is a must. The Indonesian government must be able to answer thechallenge is to strengthen national energy security. Because energy is a strategic conditions to supportnational development through the availability of sufficient, safe, and energy- quality and evenlydistributed throughout Indonesia at an affordable price, it requires a government policy that supportsnational energy security. An attempt was made by the Government of Indonesia to ensure energysecurity is to issue a policy for the use of renewable energy in Indonesia .Key Words: renewable energy, policy, national security, economic growth